Efektivitas Penanganan Keluhan Pasien Pelayanan Kesehatan di Rumah Sakit Bahteramas Sulawesi Tenggara - Suhadi, Suhadi; Maidin, Alimin; Palutturi, Sukri; Bahar, Burhanuddin; Nurmaladewi, Nurmaladewi; Astuty, Esti (Media Kesehatan Masyarakat Indonesia, 2019)
to society, but the providing service must be quality and satisfying for patients. One measure of the success of the service is a complete complaint handling system. This study aims to analyze the effectiveness of the handling of health service complaints in the Bahteramas Hospital of Southeast-Sulawesi Province. This is a qualitative research, with case-study approach. Informants are patients and staff of the hospital. Collection data conducted by in-depth interviews, observation and document review. The results indicate that the handling of complaints of health services in hospitals has not been entirely effective. In its implementation, there were still many problems including complaint-handling obstacles, unclear complaint-handling information, partly refusal complaint-handling, a slow complaint-handling, lack of officers’ sympathy, lack of complaint-handling solutions, no explanation from the officer, no complaint-handling unit. The implementation of complaints handling in Bahteramas Hospital has not been effective, there were still some problems faced, namely the aspects of service quality, organizational behavior and service resources. There are some items needed to enhance by the hodpital namely improvement of policies, service management, education and training for officers, and fulfillment of service resource needs.